Geotecnologias aplicadas à avaliação de indicadores ambientais e de desigualdade social na cidade de São Carlos – SP, Brasil - Camacho, Vitor Augusto Luizari (2022)
The rapid urban expansion of Brazilian cities has modified the natural landscape, altering the environmental conditions and generating social inequalities. The present research has as its starting point the relationship between social and environmental conditions in the urban space of São Carlos - SP, whose objective is to analyze the socio-environmental problems, such as floods, heat islands, deficiency of vegetation cover and irregular waste disposal and verify its relationships with patterns of social inequality. Using cartography and geotechnological tools, multiple indicators were mapped and synthesized into a social exclusion index. The theoretical methodological framework was the theory of urban space production, so the scale of work is the urban perimeter, where these processes are evidenced. To make the cartographies, techniques of digital image processing (DIP), remote sensing, and georeferencing of indicators and other bases were used in a geographic information system in the QGIS software. Through the cartographic products and spatial analysis it was possible to state that there is a spatial relationship between the inequality index and the environmental indicators. It was also possible to point out mitigation measures for the impacts caused by the problems in the urban space of São Carlos. From the results of this research, it is intended to demonstrate potential for replicability in other cities and scales, as well as to subsidize the formulation of public policies and environmental and urban planning, serving managers, decision-makers and social organizations.